Particularities in the technique of calvaria graft - Ramalho-Ferreira, Gabriel [UNESP]; Faverani, Leonardo Perez [UNESP]; Gaetti-Jardim, Ellen Cristina [UNESP]; Rossi, Ana Cláudia; Polo, Tárik Ocon Braga [UNESP]; Magro Filho, Osvaldo [UNESP]; Okamoto, Roberta [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2012)
Calvaria grafts provide good bone quantity for the reconstruction of the atrophic maxilla, and have lower morbidity and resorption rates when compared to iliac crest. The aim of this paper is to present the technique for obtaining a graft of the skull. Initially, the depth of the osteotomy is determined by a manually conducted bur, which establishes the limits of the structures of the skull (outer table, diploe and inner table), making the removal of bone blocks easier and safer. Thus, osteotomies of the blocks are made with greater security, avoiding the complications inherent to surgical technique. The case that will be presented it is from a male patient of 65 years who refused to submit to the iliac crest graft, opting for the calvaria, despite being bald, that is a contraindication for this treatment modality. A delicate suture associated with placement of titanium mesh to maintain the conformation of the patient's skull in the region of the bone defect, created after removal of the graft, provided a good cosmetic result at the donor site. The use of titanium mesh for re-anatomization of bone defects created in the grafts is well indicated for bald patients.

Los injertos de calvaria proporcionan una buena cantidad de hueso para la reconstrucción del maxilar atrófico, y tienen menores tasas de morbilidad y reabsorción en comparación con la cresta ilíaca. El objetivo de este trabajo es presentar la técnica para la obtención de un injerto del cráneo. Inicialmente, la profundidad de la osteotomía se determina mediante una fresa manualmente, lo que establece los límites de las estructuras del cráneo (tabla externa, diploe y tabla interna), lo que hace la eliminación de bloques óseos más fácil y segura. Por lo tanto, las osteotomías de los bloques se hacen con mayor seguridad, evitando las complicaciones inherentes a la técnica quirúrgica. Se presenta el caso de un paciente hombre de 65 años que se negó a ser sometido a injerto de cresta ilíaca, optando por la bóveda craneal, a pesar de ser calvo, que es una contraindicación para esta modalidad de tratamiento. Una sutura cuidadosa asociada con la colocación de malla de titanio para mantener la conformación del cráneo del paciente en la región del defecto óseo creado después de obtención del injerto, deja un buen resultado cosmético en el sitio donante. El uso de malla de titanio para la re-anatomización de defectos óseos creados en los injertos está bien indicada para pacientes calvos.
Particularidades en la técnica quirúrgica de injerto de calota
Keywords: Skull; Jaw; Atrophy; Osteotomy